Identifikasi Bakteri Tahan Asam (BTA) pada Pasien Suspek Tuberculosis di Puskesmas Ngronggot, Kabupaten Nganjuk, Jawa Timur - Yuliana Prasetyaningsih; Yona Yualita Kalisty; Eni Kurniati (LPPM STIKES Guna Bangsa, 2015)
Tuberculosis (TB) is an infectious disease caused byMycobacterium tuberculosis that can invade the lungs as a primary infection which is a major health problem in developing countries. The purpose of this study to identification Acid Resistant Bacteria in patients with symptoms of tuberculosis in the region Ngronggot health center, district Nganjuk. This type of study was a descriptive study. The sample in this study is the sputum of patients with suspected tuberculosis. The study was conducted in district health centers Nganjuk Ngronggot on May 14 to June 30, 2012 were 116 patients with symptoms of cough for more than three weeks and gained 7.76% or 9 people who suffer from tuberculosis with positive sputum smear examination. And the obtained results of 92.24% or 107 people with negative sputum smear examination.